2016
DOI: 10.1134/s1607672916030194
|View full text |Cite
|
Sign up to set email alerts
|

The level of cytokines and expression of caspase genes in rheumatoid arthritis

Abstract: The level of TNFα and IL6 in the blood plasma of patients with rheumatoid arthritis (RA) who received antiinflammatory therapy with methotrexate (MT) was significantly lower than in the patients without MT treatment. The level of caspase 6 and 9 gene transcripts in peripheral blood lymphocytes in patients with rheumatoid arthritic diagnosed for the first time and in patients with MT treatment were not significantly different. At the same time, the level of caspase 3 mRNA expression was significantly higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Therefore, it is possible that the discrepancy between the findings in this in vivo study and the previous in vitro study may be due to the differences in IL‐6 and TNF‐α concentrations. According to Malysheva et al ., 24 plasma IL‐6 and TNF‐α concentrations in patients with RA under methotrexate treatment were 8.89 ± 1.34 pg/mL and 3.62 ± 0.99 pg/mL, respectively, which did not differ greatly from our findings. Hence, inflammatory cytokines may have little effect on OATP1B activity at plasma concentrations of patients with RA.…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, it is possible that the discrepancy between the findings in this in vivo study and the previous in vitro study may be due to the differences in IL‐6 and TNF‐α concentrations. According to Malysheva et al ., 24 plasma IL‐6 and TNF‐α concentrations in patients with RA under methotrexate treatment were 8.89 ± 1.34 pg/mL and 3.62 ± 0.99 pg/mL, respectively, which did not differ greatly from our findings. Hence, inflammatory cytokines may have little effect on OATP1B activity at plasma concentrations of patients with RA.…”
Section: Discussioncontrasting
confidence: 57%
“…Caspase-3 (CASP-3) is known to cause apoptosis in cells. The expression of caspase-3 mRNA in PBLs was significantly higher in MT-treated RA patients than in patients without MT [48]. Our study showed that CASP3 can be directly affected by MOL000422 and MOL003187 compounds and the gene was enriched in the three pathways of IL-17 signaling pathway, MAPK signaling pathway, and TNF signaling pathway.…”
Section: Resultsmentioning
confidence: 82%
“…For several decades apoptosis has been known to be an important vital biological process that occurs in living cells during tissue development, immune responses [ 39 , 40 ], and homeostasis [ 41 ]. Anti-apoptotic mediators can be abrogated in pathological states, as in cancer [ 42 ] and autoimmunity [ 43 ], or exacerbated, as in stroke [ 44 ], neurodegeneration [ 45 ], retinal cell death [ 46 ], rheumatoid arthritis [ 47 ], myocardial and liver ischemia [ 48 , 49 ], and inflammatory diseases such as sepsis [ 50 ], osteoarthritis (OA) [ 51 ], and asthma [ 52 ].…”
Section: Introductionmentioning
confidence: 99%